On the contribution of interest expense (income) on total output - Ahmed Mehedi Nizam (Open Economics, 2021)
A decrease in interest rate in traditional view of monetary policy transmission is linked to a lower cost of borrowing which eventually results into a greater spending in investment and a bigger GDP. However, a decrease in interest rate is also linked to a decrease in interest income which, in turn, affects the aggregate demand and total GDP. So far, no concerted effort has been made to investigate this positive inter-relation between interest income and GDP in the existing literature. Here in the ftrst place we intuitively describe the inter-relation between interest income and output and then provide a micro-foundation of our intuitive reasoning in the context of a small endowment economy with ftnitely-lived identical households. Then we try to uncover the impact of nominal interest income on the macroeconomy using multiplier theory for a panel of some 04 (four) OECD countries. We deftne and calculate the corresponding multiplier values algebraically and thenwe empirically measure them using impulse response analysis under structural panel VAR framework. Large, consistent and positive values of the cumulative multipliers indicate a stable positive relationship between nominal interest income and output.Moreover, variance decomposition of GDP shows that a signiftcant portion of the variance in GDP is attributed to interest income under VAR/VECM framework. Finally, we have shown how and where our analysis ftts into the existing body of knowledge.
Keywords: E43; E50; E52; G20; G21; 330; nominal interest expense; nominal lending rate; domestic credit; GDP; economic multiplier; monetarypolicy transmission mechanism; banking